Changes in student teachers' agency beliefs during a teacher education year, and relationships with observed classroom quality, and day-to-day experiences. - Malmberg, L; Hagger, H (2009)
BACKGROUND: Conceptualizations of teachers' agency beliefs converge around domains of support and instruction. AIM: We investigated changes in student teachers' agency beliefs during a 1 year teacher education course, and related these to observed classroom quality and day-to-day experiences in partnership schools during the practicum. SAMPLES: Out of a sample of 66 student teachers who had responded to at least two out of four times to a questionnaire (18 men 48 women; mean age 26.4 years), 30 were observed during teaching, and 20 completed a 4-day short form diary. METHODS: Confirmatory factor analysis validated two agency belief constructs. Multi-level models for change investigated individual differences in change over time. Multi-level path models related observation and diary responses to agency beliefs. RESULTS: Supportive agency belief was high and stable across time. Instructional agency belief increased over time, suggesting a beneficial effect of teacher education. This increase was predicted by observed classroom quality (emotional support and student engagement) and daily positive affect and agency beliefs. CONCLUSIONS: Teacher education is successful in creating a context in which student teachers' supportive agency beliefs can be maintained and instructional agency beliefs can increase during the course.